Endoscopic Approach in the Diagnosis of Gastrointestinal Acute Graft Versus Host Disease in Children. Issue 1 (24th February 2022) - Faraci, Maura; Giardino, Stefano; Madeo, Annalisa; Coccia, Cristina; Arrigo, Serena; Pierri, Filomena; Gandullia, Paolo
Abstract : Objectives: The objectives of this study were to describe clinical, histological, and endoscopic findings in children undergoing gastrointestinal (GI) endoscopy for symptoms of digestive acute graft-versus-host disease (a-GvHD), to evaluate the rate of steroid-resistant GvHD and transplant-related mortality, and to describe the feasibility and safety of the endoscopic procedure. Methods: This was a retrospective study conducted, at the IRCSS Istituto G. Gaslini in Genova, Italy, in 26 children undergoing upper or lower GI endoscopy after allogeneic hematopoietic stem cell transplantation between 2000 and 2017. Results: Histology confirmed a diagnosis of a-GvHD in 73% of patients; it was frequently associated with steroid-resistant a-GvHD ( P = 0.001) and with an increased transplant-related mortality. Additionally, one patient developed duodenal hematoma after endoscopy for a high-grade GI a-GvHD. Conclusions: In our experience, the endoscopic approach in the diagnosis of GI a-GvHD in children was feasible and safe. Furthermore, the histological diagnosis of GI a-GvHD was associated with an increased risk of steroid-resistant GvHD and with high transplant-related mortality.